Kepemimpinan Transformasional dalam upaya Kepala Madrasah Mentransformasi Karakter Pelajar Pancasila di MA Nurul Qur’an - Arbi'ah, Amien; Sulton, Sulton (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This research aims to analyze the transformational leadership style of the madrasah principal in implementing the Project for Strengthening the Pancasila Student Profile (P5) at MA Nurul Qur’an. The main focus of this study is how the dimensions of idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration are used to transform student character amidst digital era challenges. This research employs a qualitative approach with a case study design. Data collection was carried out through in-depth interviews, participatory observation, and documentation. Research findings indicate that the madrasah principal successfullyintegrated pesantren religious values with the Pancasila Student dimensions through real modeling and persuasive vision communication. Intellectual stimulation encouraged teachers to innovate in character learning, while individualized consideration provided space for students' personal development. The conclusion of this study is that an adaptive transformational leadership model can strengthen students' independent and critical reasoning characters while maintaining the madrasah's spiritual identity. The novelty of this research lies in the synchronization of Al-Qur'an literacy culture with systematic national character building.